Chapter 7 Cellular Control of Time, Size, and Shape in Development and Evolution - Schneider, Richard A. (Evolutionary Cell Biology, 2018)
The rules by which anatomical size and shape are generated have intrigued scientists for centuries. In 1638, Galileo suggested a mathematical relationship between proportional changes in the shape of bones as animals increase in size, which he argued was a functional necessity for weight bearing (1914). The formalism of Galileo, whereby, physical forces and mathematical laws became integrated with studies of size and shape in biology, was most conspicuously encapsulated over a hundred years ago in the 1917 monumental tome by D'Arcy Thompson entitled, On Growth and Form (Thompson 1917). In a breathtakingly comprehensive manner, Thompson synthesized the observations of numerous predecessors and contemporaries, and through countless examples built a theoretical and experimental framework for describing changes in morphology that persists to this day (Stern and Emlen 1999; Arthur 2006).